Synchronous malignant multicentric cerebral glioma with atypical neuroradiological presentation and comparatively long survival: Case report and literature review - Perić, Predrag; Pavlićević, Goran; Ostojić, Jelena; Kostić, Dejan; Nikolajević, Sanja; Šupić, Gordana; Magić, Zvonko; Radovinović-Tasić, Sanja (Vojnosanitetski pregled, 2020)
Introduction. Synchronous multicentric cerebral gliomas are uncommon brain tumors, mostly malignant, with unknown pathogenesis, unfavorable prognosis and still controversial management. Preoperative differentiation from other multiple brain pathologies by conventional magnetic resonance imaging (MRI) is often difficult, but supplemental use of advanced magnetic resonance techniques should allow the tumor biology to be predicted and an appropriate treatment strategy planned. Case report. We reported a 59-year-old man with double synchronous multicentric cerebral lesions, which had initial MRI and diffusion-weighted imaging presentation as left parietal metastasis and ipsilateral amygdalo-hippocampal low-grade glioma. However, magnetic resonance spectroscopy (MRS) of both lesions showed different metabolite profiles of malignant glioma. En bloc resection of the easily accessible parietal lesion revealed glioblastoma with methylated O6-methylguanine-DNA methyltransferase (MGMT) gene promoter. Subsequently, the patient was treated with temozolomide (TMZ)-based chemoradiation according to Stupp’s protocol, with continuous standard (5/28) adjuvant TMZ in 12 courses. Despite prolonged stabilization of the disease with good life-quality during treatment, the patient died 19 months after diagnosis. The time to tumor progression estimated by MRI was 17 months. Conclusion. MRS significantly improved the differential diagnostic accuracy of conventional MRI in our patient. In accordance with reviewed literature data, the younger age, good initial performance status and methylated MGMT gene promoter were all favorable predictors of longer survival in the reported case. Resection of at least one easily accessible tumor lesion, followed by TMZ-based chemoradiation, with continuous adjuvant TMZ in more than 6 standard courses, seems currently to be the most beneficial therapeutic option for such cases.